2013
DOI: 10.1177/0897190013514090
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Testers in Multidisciplinary Health care Team Expand HIV Point-of-Care Testing Program

Abstract: Knowledge of HIV serostatus is the first step to accessing treatment, reducing transmission, and mitigating public health challenges. We describe the expansion of an HIV point-of-care testing (POCT) program within a health care system utilizing pharmacists as testers. The testing program's expansion is detailed and its impact assessed. The POCT program was evaluated by comparing the number of traditional HIV venipuncture tests to the number of POCTs performed across the health system as well as comparing the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Previous research has shown that POC testing is an effective way for pharmacists to help manage acute and chronic disease states as part of an interprofessional team to improve quality of patient care. 7,15 Building upon the established value of the service, successful implementation of POC testing into an existing practice requires strategic design and informed decision-making. The results of this study provide pharmacists intending to incorporate POC testing into their community practice with a practical roadmap to start.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that POC testing is an effective way for pharmacists to help manage acute and chronic disease states as part of an interprofessional team to improve quality of patient care. 7,15 Building upon the established value of the service, successful implementation of POC testing into an existing practice requires strategic design and informed decision-making. The results of this study provide pharmacists intending to incorporate POC testing into their community practice with a practical roadmap to start.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, retention rates (19% lost to follow-up, and 25% dropout rate) were as good as or better than other reports of retention in PrEP services, which is a real challenge in providing successful PrEP services 63,64 . There are several studies (Table 2) that report successful HIV testing performed by pharmacists, most in the community pharmacy setting, including in marginalized populations such as minorities and low-income groups [65][66][67][68] . These testing interventions by pharmacists were well accepted and also appeared to be cost-effective 69,70 .…”
Section: Hiv Prevention and Prepmentioning
confidence: 99%
“…21,22 Pharmacists in community and outpatient settings perform point-ofcare HIV tests, provide pretest and posttest patient counseling, counsel patients with a positive result about confirmatory testing, and facilitate a linkage to care. 23 CDC is developing a toolkit for HIV testing in community pharmacies and retail clinics, and the Michigan Pharmacists Association offers an accredited certificate course for pharmacists focused on point-of-care testing in community pharmacies. 24 These training modules set forth a curriculum designed to support pharmacists in the administration of point-of-care HIV testing, including competencies in pretest and posttest patient counseling, performing the actual test, reading and interpreting the HIV test results, and identifying sites for linkage to care and confirmatory testing.…”
Section: Pharmacist Involvement In Hiv Testingmentioning
confidence: 99%